Advances in CpG Island Methylator Phenotype Colorectal Cancer Therapies - Zhang, Xiaofei; Zhang, Wenjun; Cao, Pingan (Frontiers in Oncology, 2021)
With the aging of the population, the incidence of colorectal cancer in China is increasing. One of the epigenetic alterations: CpG island methylator phenotype (CIMP) plays an important role in the incidence of colorectal cancer. Recent studies have shown that CIMP is closely related to some specific clinicopathological phenotypes and multiple molecular phenotypes in colorectal cancer. In this paper, the newest progress of CIMP colorectal cancer in chemotherapeutic drugs, targeted agents and small molecular methylation inhibitors are going to be introduced. We hope to provide potential clinical treatment strategies for personalized and precise treatment of colorectal cancer patients.